2015
DOI: 10.1016/j.respe.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of women reporting poor mental health during pregnancy: Findings from the 2010 French National Perinatal Survey

Abstract: This study showed strong associations between many socially disadvantaged characteristics and a positive dimension of mental health. The findings suggest that well-being measures such as self-rated mental health should be routinely assessed during pregnancy so that women can be offered more appropriate support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
1
13
0
6
Order By: Relevance
“…The prevalence of women reporting depressive symptoms was similar during pregnancy and post‐partum (11.8/12.1%), and women (around 30%) reported a very good perceived mental health, both during pregnancy and after childbirth. Less than very good mental health could indicate other symptoms than depressive symptoms such as anxiety and eating disorder . The prevalence of depressive symptoms in the current study is in line with previous studies that have found that the prevalence of prenatal depression (12%) is almost the same as post‐partum depression .…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of women reporting depressive symptoms was similar during pregnancy and post‐partum (11.8/12.1%), and women (around 30%) reported a very good perceived mental health, both during pregnancy and after childbirth. Less than very good mental health could indicate other symptoms than depressive symptoms such as anxiety and eating disorder . The prevalence of depressive symptoms in the current study is in line with previous studies that have found that the prevalence of prenatal depression (12%) is almost the same as post‐partum depression .…”
Section: Discussionsupporting
confidence: 91%
“…Perinatal care is a special health issue because it is both a time of increased vulnerability and a time of privileged sensitization. During the regular antenatal care consultations, practitioners should systematically consider social or environmental risk factors because they are as decisive as biomedical risk factors for perinatal health ( 42 ). Social risk factors could include couple situation during pregnancy, maternal employment, and type of health insurance ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a transition period with significant physical and emotional changes (5). These changes, which occur even in healthy pregnant women, affect both the quality of life and sleep quality of the pregnant women and affect the health of both mother and baby (6,7). In the light of the developments in mental health field, it was reported that psychiatric problems were common during pregnancy in the last 3 decades.…”
Section: The Effect Of Endocrinological Parameters On Sleep Quality mentioning
confidence: 99%